Effect of Work Discipline and Employee Career Development on Work Productivity Employees PT. Star - Anggriani, Catelin; Syawaluddin, Syawaluddin; Putra, Aidil; Goh, Thomas Sumarsan (Management Studies and Entrepreneurship Journal (MSEJ), 2023)
Bintang is engaged in selling fast moving consumer goods and is supported by as many as 101 employees. Employees become slow in work and also employees who are usually passionate in work for now look sluggish to work. In the company, there are problems with employee discipline in carrying out various jobs assigned to them. In the company, there are problems in employee career development where employees judge that the opportunity for him to have a career in the company is long enough. This research applies quantitative descriptive research. The total population used in this research were 101 employees with the technique of data sampling, the Slovin formula, consisting of 81 samples. There is a simultaneously significant influence between the variables of work discipline and career development toward the work productivity of PT. Bintang. Meanwhile, partially, it was found that the work discipline variable had a significant influence toward the work productivity of PT. Bintang. Partially found career development variables give a significant influence toward the work productivity of employees of PT. Bintang. The study results reveal that career development variables give more influence than work discipline on the work productivity of PT. Bintang. Keywords: Work Discipline, Career Development, Work Productivity